2021
DOI: 10.3390/agronomy11112103
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Drought–Flood Abrupt Alternation on Morpho-Agronomic and Nutrient Use Traits in Rice

Abstract: The frequent occurrence of drought–flood abrupt alternation (DFAA) in Huaibei Plain has shown a great impact on local rice production. Pot experiments were performed in 2016–2018 to investigate the effects of co-occurring drought and flooding stresses on dry weight (DW), grain yield, nitrogen (N), phosphorus (P) and potassium (K) uptake and use efficiencies (NUE, PUE and KUE) in rice. The results showed that DFAA changed the accumulation of biomass and nutrients among different organs in rice. Compared with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…processing results will be better, and 9). Drought factors have a big influence on rice growth, nutrient utilization and crop yields [17].…”
Section: Resultsmentioning
confidence: 99%
“…processing results will be better, and 9). Drought factors have a big influence on rice growth, nutrient utilization and crop yields [17].…”
Section: Resultsmentioning
confidence: 99%
“…(2019) reported additively reducing effects of drought and flooding stress on rice yield, two other studies found a compensation for flooding‐related yield loss by a previous drought period (Gao et al., 2019; Huang et al., 2019). The increase in root formation through drought was reversed in the flooding period, dampening the positive effects mild drought can have on crop yield (Huang et al., 2019, 2021). In Arabidopsis, the stress response is largely accession‐specific.…”
Section: Flooding Stress In Combination With Other Stressesmentioning
confidence: 99%
“…A study [27] showed that the yield reduction rate of DFAA at the jointing stage was between 20% and 50% and that the yield reduction of the severe drought and severe flood group was the greatest. From the perspective of yield composition, some studies have suggested that the main reason for yield reduction is a reduction in the number of effective panicles and the number of grains per panicle, and some studies have suggested that it is related to a decrease in the seed setting rate [28,29]. In this study, the yield reduction range of DFAA was 5.1-39.65%, and the reduction in grain number and grain weight was the main factor influencing yield reduction.…”
Section: Interaction Effect Of Dfaa On Rice Yieldmentioning
confidence: 99%